A comparative evaluation of portable Doppler ultrasound versus electrocardiogram in heart-rate accuracy and acquisition time immediately after delivery: a multicenter observational study. (3rd July 2021) - Agrawal, Gopal; Kumar, Anil; Wazir, Sanjay; Kumar, N. Chandra; Shah, Piyush; Nigade, Amit; Nagar, Nandini; Kumar, Surender; Kumar, Kishore
Abstract: Background: The assessment of newborns' heart rate (HR) in the delivery room is one of the important steps to ascertain the need for initiation and continuation of resuscitation. At present, ECG is the "gold standard" to monitor neonatal HR in the delivery room. However, various limitations with the use of ECG exist. Furthermore, in developing countries, ECG may not be universally available in delivery rooms. Objective: To compare the accuracy and HR acquisition time of portable Doppler ultrasound (PDU) versus electrocardiogram (ECG) in newborns. Methods: This multicenter, prospective, observational study across five centers in India between January and September 2017 included neonates more than 34 weeks of gestation ( n = 131) delivered by cesarean section. The accuracy of HR recorded by PDU (HRPDU ) versus that by ECG (HRECG ) was the primary outcome. Secondary outcomes included time to acquisition of an audible and/or visible signal and device application. Results: Mean (±SD) gestational age and birthweight were 37.7 (±1.2) weeks and 2954 (±457) g, respectively. The mean (±SD) visible HRPDU was 158 (±21) bpm versus HRECG of 161.3 (±20) bpm ( p = .07) which were comparable. The median (1st, third quartile) time to acquisition of audible HRPDU (76 [51, 91] s), was significantly shorter than that of HRECG (96.5 [74.2, 118] s; p < .001). Conclusion: Portable Doppler has similar accuracy to ECG and is faster in acquiring the signal.